If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -24 + -9y + 31 = 0 Reorder the terms: -24 + 31 + 4y + -9y = 0 Combine like terms: -24 + 31 = 7 7 + 4y + -9y = 0 Combine like terms: 4y + -9y = -5y 7 + -5y = 0 Solving 7 + -5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5y = 0 + -7 -5y = 0 + -7 Combine like terms: 0 + -7 = -7 -5y = -7 Divide each side by '-5'. y = 1.4 Simplifying y = 1.4
| -4(y-3)=6y-38 | | f(-2)=-2+2(-2-1) | | -9x+-18+25=-38 | | 3+(-22)= | | 7-11x=x-33 | | 3log(7)(4)-5log(7)(m)= | | f(3)=3+2(3-1) | | -2x-10=44+8x | | 5t-2t=t | | 2z^2+7x=0 | | -4(2-y)+3y=4(y-4) | | (2x+4)(x-3)=0 | | f(-2)=-3(4-2)+2 | | 2x-3=4y+6 | | 4x^2-6x+5=x+1 | | 210x+100-72x^2=0 | | -9+4-(-5)= | | 8-3a^3=0 | | f(3)=-3(4-3)+2 | | X-6+2x=48 | | 64=-3(1-2n) | | 2x^2+28x+74=0 | | -65=136 | | 9z^2-26z-3=0 | | 18-7x=5(3x-2)+6 | | 3.6k+1.6k+20.8=-26 | | 1x+4x=x+8 | | -3v-5=2(v-5) | | X+x+3=15 | | 13n-4=22 | | (63b)*2= | | 1.5x=1.5 |